The effect of gamma irradiation on chemical, morphology and optical properties of polystyrene nanosphere at various exposure time - Yabagi, Jibrin Alhaji; Kimpa, Mohammed Isah; Muhammad, Muhammad Nmayaya; Rashid, Saiful; Embong, Zaidi; Agam, Mohd Arif (IOP Publishing, 2017)
Irradiation of polymers causes structural, chemical and the optical properties changes. Polystyrene nanosphere was drop coated to substrates and the gamma irradiation was carried out in a Cesium-137 (Cs-137) source chamber at different time (1-5 hours) with constant dose of 30 kGy. Fourier transformation infrared spectroscopy (FTIR) and Raman spectroscopy were employed to characterize the chemical properties of irradiated polystyrene while Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) were used to study the surface morphological changes of the samples. The optical energy band gaps of the thin films were investigated and studied using transmittance and absorbance measurements. The results obtained revealed that as irradiation time increases the optical properties changes and polystyrene gradually undergoes crystal to carbonaceous from its amorphous state. The average particles diameter and roughness of the samples decreases with increasing irradiation time.